Annotated checklist of Gonyleptoidea (Opiliones: Laniatores) associated with Brazilian caves - de Ázara, Ludson Neves; Ferreira, Rodrigo Lopes (Zootaxa, 2018)
In Brazil, the order Opiliones has been well studied, making this country the leader in research with the group, but few extensive works have been made on the distribution of harvestmen associated with caves. In this context, the present paper aims to list all records of the superfamily Gonyleptoidea associated with Brazilian caves, using records from the literature and unreported data from scientific collections. The compiled checklist contains the largest number of harvestmen species recorded for caves in one country, worldwide. A total of 155 species belonging to 7 families were recorded from 952 caves throughout 152 municipalities and 17 states of Brazil. A considerable number of 46 putative (undescribed) new species were recognized, including 9 troglomorphic species. Additionally, 161 new municipal records where found for 58 known species. The most diverse family was Gonyleptidae (104 spp.), with the subfamilies Pachylinae (55 spp.), followed by Goniosomatinae (18 spp.) and Mitobatinae (16 spp.). The number of described species analysed in the present work represents about 12% of the Brazilian opiliofauna of Gonyleptoidea, with many species widely distributed, being indicative of affinity of the group with the cave environments. Thus, the compilation of distribution data of such species (mainly the troglobitic and troglomorphic) can directly contribute to a higher valuation of their habitats, leading to better preservation policies, as well as being useful for future ecological and biogeographical studies.